2022
DOI: 10.1007/s40264-022-01265-1
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Drug Interaction Errors and Misunderstandings: Recommendations for Improved Evidence-Based Management

Abstract: Colchicine is useful for the prevention and treatment of gout and a variety of other disorders. It is a substrate for CYP3A4 and P-glycoprotein (P-gp), and concomitant administration with CYP3A4/P-gp inhibitors can cause life-threatening drug–drug interactions (DDIs) such as pancytopenia, multiorgan failure, and cardiac arrhythmias. Colchicine can also cause myotoxicity, and coadministration with other myotoxic drugs may increase the risk of myopathy and rhabdomyolysis. Many sources of DDI information includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…76,77 Nonfibrate therapy for triglyceride lowering should be preferred for concomitant use with colchicine. 78 Other cardiovascular medications that interact with colchicine include amiodarone, dronedarone, quinidine, and propafenone. 7,75 Concomitant use of these antiarrhythmic agents with colchicine should involve collaborative monitoring with an electrophysiologist.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…76,77 Nonfibrate therapy for triglyceride lowering should be preferred for concomitant use with colchicine. 78 Other cardiovascular medications that interact with colchicine include amiodarone, dronedarone, quinidine, and propafenone. 7,75 Concomitant use of these antiarrhythmic agents with colchicine should involve collaborative monitoring with an electrophysiologist.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…There is no recommendation for dose adjustment in mild to moderate renal impairment (estimated creatinine clearance 30–80 mL/min); however, close monitoring for adverse outcomes in these groups is advised 24 25. Lastly, (3) drug interactions,13 14 23 26 particularly when co-administered with CYP3A4 or P-gp inhibitors 6 27. Both transporter (P-gp) and metabolising enzyme (CYP3A) share an extensive range of substrates; therefore, the disposition of drugs is influenced by both mechanisms simultaneously 28.…”
Section: Discussionmentioning
confidence: 99%
“…109 In addition, when CYP3A4 inhibitors are used in combination with colchicine, it may promote the intracellular accumulation of colchicine, eventually leading to toxic effects such as muscle pain, vomiting, diarrhea, exacerbated infections, and abnormal bleeding. 110 Glucocorticoids. The word glucocorticoid is a portmanteau from a combination of words glucose, cortex, and steroid, owing to its function in regulating glucose metabolism and synthesis in the zona fasciculate of the adrenal cortex, and is a class of steroid hormones.…”
Section: ■ Treatment Strategies For Goutmentioning
confidence: 99%
“…Studies have shown that concurrent administration of interacting drugs or use of colchicine in patients who have renal impairment possess myopathy or rhabdomyolysis . In addition, when CYP3A4 inhibitors are used in combination with colchicine, it may promote the intracellular accumulation of colchicine, eventually leading to toxic effects such as muscle pain, vomiting, diarrhea, exacerbated infections, and abnormal bleeding …”
Section: Treatment Strategies For Goutmentioning
confidence: 99%